NR coregulators and human diseases - Kumar, Rakesh (World Scientific Pub. Co., 2008)
This book serves as a treasure for all those who have an interest in nuclear receptor coregulators and human diseases. Written by experts in the field, each chapter provides comprehensive, up-to-date information on the physiologic and pathologic roles of coregulators in specific organ systems, giving biomedical students; basic and clinical researchers; and educators in diverse sub-specialties a thorough summary of the overall subject. Readers will be able to understand the important current information and views on specific coactivators and corepressors and their roles in the pathogenesis of human diseases in areas outside their own expertise or experience. A special emphasis is placed on the "classic" papers as well as perspectives on future directions for the field